2020
DOI: 10.1038/s41576-020-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

The road ahead in genetics and genomics

Abstract: In celebration of the 20th anniversary of Nature Reviews Genetics , we asked 12 leading researchers to reflect on the key challenges and opportunities faced by the field of genetics and genomics. Keeping their particular research area in mind, they take stock of the current state of play and emphasize the work that remains to be done over the next few years so that, ultimately, the benefits of genetic and genomic research can be felt by everyone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 132 publications
(134 reference statements)
0
88
0
1
Order By: Relevance
“…When incorporating population data, it is also important for fairness and equity to understand how it changes the accuracy of methods for individuals with ancestries outside of those used in the development of the population resources. It is known that many genomic databases have collected more data for the European population than others [16][17][18]. We demonstrate that even using frequencies from a genetically distinct population, the population-aware model still performs similarly as the baseline.…”
mentioning
confidence: 83%
“…When incorporating population data, it is also important for fairness and equity to understand how it changes the accuracy of methods for individuals with ancestries outside of those used in the development of the population resources. It is known that many genomic databases have collected more data for the European population than others [16][17][18]. We demonstrate that even using frequencies from a genetically distinct population, the population-aware model still performs similarly as the baseline.…”
mentioning
confidence: 83%
“…The high prevalence of HbC in West Africa, even though HbS associated genotypes are known to demonstrate excess of average fitness higher than HbC associated genotypes, indicate that HBB-β S is recent in this West African region ( F ); This needs to be properly investigated from an evolutionary genetic point of view. Lastly, from the time HBB-β S attained equilibrium in populations [currently estimated at 5000 years ago ( 1 )], it is likely that the pressure because of SCA on the human genome could have contributed to the enrichment of additional adaptive signatures, that still need to be investigated, as suggested by the enrichment of recurrent variants in numerous genes that are relevant to pathophysiology of SCD among patients in Africa ( 57 ).…”
Section: Common Variants In Haemoglobin Genesmentioning
confidence: 99%
“…Other loci recently associated with HbF level include BCL2L1 (OMIM: 600039, 20q11.21) ( 54 ) (which is yet to be replicated in Africa), and FRMPD4 (OMIM: 300838, Xp22.2) found among patients living with SCD in Tanzania ( 55 ). While, it is estimated that the HbF trait is highly heritable (87%) ( 56 ), the current known catalogue of variants explain just ~20–50% of the HbF phenotypic variance, indicating that many more variants remain to be uncovered, particularly in African populations, which harbour the highest genetic diversities with usually more extreme phenotypes ( 57 ). A particularly interesting new area of research would be to perform genome scans of SCA patients, particularly the long-term survivors, for signatures of adaptation, with specific interest to genomic loci involved in stage-specific expression of globin genes.…”
Section: Common Variants In Haemoglobin Genesmentioning
confidence: 99%
“…The forecasting or designating genotypes that cannot be assayed directly in individuals’ samples are known as genotype imputation ( Ashburner et al, 2000 ; Naj, 2019 ; Chen S. F. et al, 2020 ). In recent years, the studies on genome-wide association (GWA) have revealed many significantly replicated associations for various complicated diseases ( McGuire et al, 2020 ). In the analysis of GWA studies, genotype imputation has been widely used to enhance power, fine-map connections, and expedite the integration of results throughout the studies using meta-analysis.…”
Section: Identification Of Therapeutic Biomolecules Of Plants Through the Multi-omics Approachmentioning
confidence: 99%